Genome-wide DNA methylation patterns for indicators of liver steatosis: a longitudinal multiomic study - Ciantar, Jo; Rajić, Sonja; Kostiniuk, Daria; Raulamo, Ella; Kartiosuo, Noora; Lai, Liye; Mishra, Pashupati P.; Lyytikäinen, Leo-Pekka; Kleber, Marcus E.; Rovio, Suvi; Mykkänen, Juha; Pahkala, Katja; et al. (Springer Nature, 2026)
Background
To identify blood DNA methylation profiles related to liver steatosis, we performed an EWAS on the presence of ultrasonically-identified liver steatosis in the Young Finns Study (YFS) participants (n = 1529, 33–50y.), and on liver enzyme levels and fatty liver index (FLI) across three discovery cohorts: YFS, LURIC (n = 2371, 17–92y.) and KORA FF4 (n = 1872, 39–88y.). We further investigated the discovered associations across the longitudinal subset of YFS (n = 255), encompassing three follow-ups over 32 years, and the three-generational YFS-3G follow-up in 2018–2020. Finally, we examined the associations of the discovered CpGs with nearby genetic variation and whole blood expression of nearby genes.
Results
In YFS, the methylation levels of cg06690548 (SLC7A11) were lower in individuals with liver steatosis (Δbeta = − 0.011, FDR = 0.004). Methylation of 9 CpGs associated with GGT and 23 CpGs with FLI in at least two of the discovery cohorts. Methylation at cg06690548 (SLC7A11) and the majority of the CpGs associating with GGT or FLI had the strongest association in the two oldest generations of YFS-3G follow-up (ages 43–59y. and 59–93y.), with minor or non-significant association in the youngest generation (ages 6–36y.). Discovered meQTLs for the CpGs did not modulate the association between the methylation levels and GGT or FLI. The expression of the nearby genes mediated only the association between cg06500161 (ABCG1) and cg20544516 (SREBF1) and FLI.
Conclusions
Our findings highlight the association between the methylation levels of cg06690548 (SLC7A11) and liver steatosis, describe the dynamic relationship between whole blood DNA methylation and MASLD, and contribute to a deeper understanding of the pathophysiology of liver diseases.